Sensing The Birth Preferences Among Spouses Of Rural And Urban Kano, Kano State, Nigeria - Lambu, Ibrahim Badamasi; Dan, Yakubu (Advances in Social Sciences Research Journal, 2015)
The paper addresses the spatial variation in term of preferences of children (number, composition and sex) among families in rural and urban areas of Kano state. The causes, effects and implications are explored in the paper. Critical social sciences paradigm is adopted to give this study a methodological underpinning. Problems of marginalization, domination and subjectivity are critically examined between genders. The study involves both quantitative and qualitative data that is the family size; income and age are quantitative while the preferences of sexes are held qualitative. Kano municipal LGA and Tofa LGA are purposively sampled to represent urban and rural environments respectively. Questionnaires and interviews are employed in collecting the data for the study. Descriptive statistics like measure of Central Tendencies were used. The finding shows high birth preference in rural areas than in the urban areas of Kano state. Male children are preferred most in both rural and urban settings. In the urban areas traditional title holders, business men and lower salary earners begets more children than the educated elites while in the rural setting, low income earners especially farmers, primary teachers and wealthy individuals abhor more children with preference to sons than daughters. Some of the reasons attached include assistance at home, farm and source of security at old age as well as heirs of family continuity. Many families tend to give birth to large number of children in the quest of getting a son(s) especially if the early children are females. Similarly if the co-wives have many males hence competition often arises each trying to have modal set. Socio-economic and socio-cultural status show some variation in the trend where couples with high level of education have less children and with lesser corresponding sex preferences than uneducated spouses. Preferences of sex and many children are more common to polygamous couples than in monogamous family. Urban areas show desire for fewer children than rural areas from both elites and masses.